CFD modeling of a compact reactor for methanol synthesis: Maximizing productivity with increased thermal controllability - Son, Minji; Woo, Yesol; Kwak, Geunjae; Lee, Yun Jo; Park, Myung June (International Journal of Heat and Mass Transfer, 2019)
A kinetic model for methanol synthesis was validated for a conventional fixed-bed reactor at the mini-pilot scale by determining a heat transfer coefficient to fit the experimental data satisfactorily. To enhance the thermal controllability of the reaction system, a compact reactor, which utilizes heat transfer with both cooling media and cool feed gas, was introduced. The analysis of detailed profiles of mass, momentum, and heat was conducted by applying the developed kinetic model to the computational fluid dynamics modeling approach. While the accumulation of heat was observed in a conventional reactor because of its limited heat transfer capability, a compact reactor could efficiently remove the generated heat. The space velocity and feed temperature were manipulated to increase the production rate while unstable thermal behavior was prevented, and it was clearly shown that the proposed reactor could produce twice the methanol, with its peak temperature maintained below the conventional one. When the diameter of the catalytic bed in the compact reactor was increased, the reaction remained in the kinetic regime, resulting in high methanol productivity as well as maximum utilization of the bed.
Keywords: Compact reactors; Computational fluid dynamics modeling; Conventional reactors; Heat transfer capability; Methanol synthesis; Peak temperatures; Thermal behaviors; Thermal control; Compact reactor; Computational fluid dynamics; Methanol; Modeling; Thermal control